Student-Perceived Benefit On The Use Of Technology Applied By Teachers In The Learning Process Of Moral Aqidah - Yusuf, Muh; Irawan, Heri (JUPE : Jurnal Pendidikan Mandala, 2023)
This study aims to describe the use of technology in the learning process in the eyes of students in the classroom and find out the level of use of technology in the learning process. This type of research is quantitative with a survey approach. The respondents to this research were students of MTs Negeri Sinjai, Sinjai Regency, South Sulawesi. The data analysis of this study is descriptive statistics. The results of this study outline that school facilities are considered very adequate and there are good teacher skills in using and applying educational technology in the learning process, especially in the field of moral aqidah studies. Quantitative descriptive results reveal that students' perceptions in the use of technology applied by teachers are adequate (capable).